Fiscal Decentralization and Poverty Reduction: Citizens View - Azila-Gbettor, Edem Maxwell; Adjimah, Harrison Paul; Tibu, Serlom Kwame (Journal of Social Economics Research, 2014)
This study intends to corroborate the positive theoretical relationship between fiscal decentralization and poverty reduction (Crook and Manor, 1998; Moore and Putzel, 1999; World Bank, 2001) base on non-monetary measurement. A qualitative research method was applied for the study. Focus group discussions was conducted using one-hundred and thirty (130) stakeholders in the community divided into five (5) area councils. The study revealed participants clear understanding of poverty. There was however, a limited support from the findings on the theoretical construct on the positive relation between fiscal decentralization and poverty reduction using non-monetary measurement. It was therefore recommended authorities must tackle both economic and social dimensions in any policy definition in order to achieve success at poverty reduction.